Antimicrobial susceptibility of Staphylococcus spp. goat mastitis isolatesin semi-intensive and extensive production systems - Gortari Castillo, Lihuel; Steffen, Kevin Denis; Buldain, Daniel; Marchetti, Maria Laura; Mestorino, Nora (Spei Domus, 2025)
Introduction: Goat milk production has experienced sustained growth in recent years. Subclinical mastitis, a disease caused mainly by Staphylococcus spp., has a high economic and health impact at a global level. However, there is little information on the antimicrobial susceptibility of these pathogens, a fundamental aspect of successful therapy. The objectives of this study were to determine the occurrence of subclinical mastitis due to Staphylococcus spp. in semi-intensive and extensive systems and to evaluate the antibacterial susceptibility in S. aureus and scn isolated from milk of goats with subclinical mastitis. Methodology: We worked with 200 goats in the extensive system and 104 in the semi-intensive system. Using the California Mastitis Test, 55 and 95 goats suspected of subclinical mastitis were selected from both systems, respectively. Milk samples were obtained and cultured in CHROMagar™ Staph aureus®. S. aureus and scn were identified by color, metabolic, and biochemical tests. Antimicrobial susceptibility was evaluated by the agar diffusion method. Results: scn were the main microorganisms isolated in both systems, presenting greater resistance to penicillin, erythromycin, and gentamicin. There was only multiple resistance phenotype in the semi-intensive system. S. aureus presented multiple phenotypes in both systems. The percentages of antimicrobial resistance found in the extensive system were significantly higher than in the semi-intensive system (p = 0.0016). Conclusions: These findings reflect the importance of implementing prudent use of antimicrobials under professional supervision, as occurs in semi-intensive treatments, and the need to monitor antimicrobial susceptibility in a sustained manner.